Antimicrobial Activity of Aloe sinkatana - ABUBAKER ALI; ELHAM ABDELBASIT SULEIMAN; AMIR SAEED; GUNNAR SANDSTRÖM (Indonesian Society for microbiology, 2013)
Aloe sinkatana is a plant belonging to the family Xanthorrhoeaceae, subfamily Asphodeloideae, genus Aloe. It is cultivated in the Red Sea Mountainseastern of the Sudan. In the present study, the extract of A. sinkatana leaves was screened for its antibacterial and antifungal activity. The phytochemical screening of A. sinkatana extracts was carried out using Thin Layer Chromatography (TLC) technique. Four extracts of A. sinkatana were prepared using chloroform, ethanol, methanol, and water. Antibacterial activity of the extract was performed following the cup-plate agar diffusion method. Also, the antifungal activity of the extract was tested. The result showed that the extracts of A. sinkatana leaves revealed antimicrobial activities greater than the commercial antifungal (Nystatin) which can be used for treatment of Candidiasis and ketoconazole that is used for treatment of fungal infection. The antimicrobial activity might be due to specific plant compounds, which was found to be more effective than commercial antifungal compounds. However the commercial antibiotic used for treatment of bacterial infection, displayed better antimicrobial activity than the A. sinkatana extracts. In conclusion A. sinkatana extract can be a useful treatment against fungal infections.